Deskripsi dan Analisis Hubungan antara Karakteristik, Tingkat Pengetahuan, dan Perilaku Konsumsi terhadap Minuman Fermentasi pada Mahasiswa - Augustiani, Ayu Andira; Rasmikayati, Elly (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Currently, the lifestyle encourages the younger generation to consume sweet drinks compared to healthy drinks such as fermented drinks. The purpose of this study was to determine the description of the level of knowledge and consumption behavior of students towards fermented drinks. This study uses a quantitative design with a survey method. The results showed that the majority of female respondents were 19 years old, lived in boarding houses and had pocket money of 1-2 million rupiah. The level of knowledge of students towards fermented beverages is quite good, with the most consumed fermented milk drinks on the grounds that they are delicious even though the frequency of consumption is still relatively rare. The results of the chi-square test showed a relationship between the gender variable and knowledge of the types and benefits of fermented beverages, as well as a relationship between the variable of residence with knowledge of the advantages of fermented beverages.